Attitudes of doctors and nurses to patient safety and errors in medical practice in the Gaza-Strip: a cross-sectional study. Issue 8 (5th August 2019) - Bottcher, Bettina; Abu-El-Noor, Nasser; Abuowda, Yousef; Alfaqawi, Maha; Alaloul, Enas; El-Hout, Somaya; Al-Najjar, Ibrahem; Abu-El-Noor, Mysoon
Abstract : Objectives: This study examined the attitudes of nurses and doctors to key patient safety concepts, evaluated differences and similarities between professional groups and assessed positive and negative attitudes to identify target areas for future training. Setting: Four major governmental hospitals in the Gaza-Strip. Participants: A convenience sample of 424 nurses and 150 physicians working for at least 6 months in the study hospitals. Primary and secondary outcome measures: The primary outcome measures were mean scores with SD as measured for individual items and nine main patient safety domains assessed by the Attitudes to Patient Safety Questionnaire. Secondary outcome measures were the proportions of doctors and nurses, that gave a positive response to each item, represented as percentage of each group. Results: Nurses and doctors held moderately positive attitudes towards patient safety with five out of nine domain scores >3.5 of 5. Doctors showed slightly more positive attitudes than nurses, despite a smaller proportion of doctors having received patient safety training with 37.5% compared with 41.9% of nurses. Both professions displayed their most positive patient safety attitudes in the same domains ('team functioning' and 'working hours as a cause for error'), as well as their two most negative attitudes ('importance of patient safety in the curriculum' and 'professional incompetence as a cause of error'), demonstrating significant deficits in understanding medical errors. A specific challenge will be the negative attitudes of both professions towards patient safety training for wider dissemination of this content in the postgraduate curriculum. Conclusion: Patient safety attitudes were moderately positive in both professional groups. Target of future patient safety training should be enhancing the understanding of error in medicine. Any training has to be motivating and relevant for clinicians, demonstrating its importance in ongoing professional learning.